Pengaruh Penambahan Jenis Tepung Terhadap Daya Terima Dendeng Lumat Keong Mas - Aprialdi, Muhammad Agung; Erina, Efrina; Putro, Permono Adi (Universitas Djuanda, 2022)
Jerky found in the market is generally made from beef, while jerky with other raw materials has not been found much. Dried golden snail contains 18.00% ash content, 56.61% crude protein, 5.87% fat and also 2.99% crude fiber. The processing of golden snail as a raw material in the production of creamed jerky is expected to provide functional food. The method used in this study was an experiment with an organoleptic test, namely a hedonik test by 30 semi-trained panelists. The formula used is a jerky formula that has been standardized and divided into 3 formulas, DK standardized formula, the difference is the addition of 50 grams of wheat flour in the DKT formula and 50 grams of cornstarch in DKM. The results of the hedonik test scale that has been carried out and analyzed with the friedman statistical test and continued with the tukey advanced test show that the DK0 formula is the most preferred sample by the panelists with a score of 15.50 for the color, a score of 2.83 for the aroma, a score for 2.43 on the texture and 2.50 on the taste. Based on the data, it can be seen if standardized blended jerky products without additions can be accepted by the panellist